(untitled) (Raparin Journal of Humanities (RJH), 2025)
This paper is an attempt to observe the effects of weight training by practicing the pyramid and TRX (Total Resistance Exercise) workout methods on muscle strength, body measurements, and certain functional abilities among the study participants. In addition to that, the results of this study were compared before and after training to determine the differences on each training sessions in terms of its effectiveness. Therefore, we as the researchers found the importance of conducting an experimental approach in order to accomplish the study objectives, specifically to be more precise in determining the results. Following that, a group of 14 bodybuilders were chosen intentionally for the sample, the participants were all from Rania city in Sulaymaniyah governorate. The training program lasted eight weeks which would accordingly develop the selected measures of fitness. Furthermore, the program followed a structured plan with weekly training cycles and two main phases. The intensity followed a 3:1 manner, and each muscle group, such as the chest and arms, did 16 training units, with two sessions per week. According to our findings, we have come to understand that both training methods which were employed during the study were found to be very effective on the targeted variables. Specifically, the pyramid training method was found to be particularly effective in increasing maximal strength and anaerobic respiration capacity, whereas TRX training found to be effective for enhancing stability, balance, and overall functional capacity.